2016
DOI: 10.18632/oncotarget.12812
|View full text |Cite
|
Sign up to set email alerts
|

Patient fibroblasts-derived induced neurons demonstrate autonomous neuronal defects in adult-onset Krabbe disease

Abstract: Krabbe disease (KD) is an autosomal recessive neurodegenerative disorder caused by defective β-galactosylceramidase (GALC), a lysosomal enzyme responsible for cleavage of several key substrates including psychosine. Accumulation of psychosine to the cytotoxic levels in KD patients is thought to cause dysfunctions in myelinating glial cells based on a comprehensive study of demyelination in KD. However, recent evidence suggests myelin-independent neuronal death in the murine model of KD, thus indicating defecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Disease-associated features are not always unique to the neurons and as a result, several of these phenotypes can be observed in both iNs and fibroblasts (Santambrogio et al, 2015 ; Lim et al, 2016a ). However, as iNs adopt a neuronal-like morphology and at least some functional properties of neurons, they provide an opportunity to study diseases in the cell type primarily clinically affected.…”
Section: Can Patient-derived Ins Provide An Authentic Cellular Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Disease-associated features are not always unique to the neurons and as a result, several of these phenotypes can be observed in both iNs and fibroblasts (Santambrogio et al, 2015 ; Lim et al, 2016a ). However, as iNs adopt a neuronal-like morphology and at least some functional properties of neurons, they provide an opportunity to study diseases in the cell type primarily clinically affected.…”
Section: Can Patient-derived Ins Provide An Authentic Cellular Systemmentioning
confidence: 99%
“…However, as iNs adopt a neuronal-like morphology and at least some functional properties of neurons, they provide an opportunity to study diseases in the cell type primarily clinically affected. For example, iNs derived from adult-onset Krabbe disease had the same lysosomal storage defects as the starting fibroblasts, but unique to the iNs was the abnormal neuronal branching, which may be more relevant to the clinical expression of this disorder (Lim et al, 2016a ). In fact, a few studies have now reported that disease-associated features could only be seen in iNs.…”
Section: Can Patient-derived Ins Provide An Authentic Cellular Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain MRI and GLAC activity assay are essential for patients manifesting chronic progressive corticospinal tract impaired. However, the relationship between the deficiencies in the lysosomal enzyme activities and the degree of clinical severity appears obscure [24,25] . Both the two mutations are reported in the gnomad dataset (http://gnomad.broadinstitute.org).…”
Section: Discussionmentioning
confidence: 99%
“…Although technology was improved thereby promoting the development of HCC therapy, the treatment outcomes of HCC with PVTT remains poor, as expected. Currently, sorafenib or lenvatinib, transarterial chemoembolization (TACE), TACE plus sorafenib, percutaneous radiofrequency ablation (RFA), and radiotherapy, among others, are used in the clinical treatment of PVTT, but these treatment options remain unsatisfactory (8)(9)(10). Therefore, further research is urgently needed to investigate the optimal therapeutic strategy for HCC with PVTT.…”
Section: Introductionmentioning
confidence: 99%